Joaquín Balaguer, memory, and diaspora : the lasting political legacies of an American protégé - Liberato, Ana S. Q., 1970- (Lexington Books, 2013)
"Joaquín Balaguer, Memory, and Diaspora" takes from and expands upon a growing and diversified body of scholarship on the enduring effects of authoritarian legacies among local and diasporic populations. It uncovers a relationship between memory and political pedagogy, revealing the authoritarian leadership practices that produce effective ideological strategies and that enhance authoritarian leaders' memory capital.